THE INFLUENCE OF PROFESSIONALISM AND FACILITIES ON JOB SATISFACTION WITH EMPLOYEE PERFORMANCE AS AN INTERVENING VARIABLE IN NORTH BINJAI DISTRICT - Ahmad Mahadi Harahap; Kiki Farida Ferine (Lafadz Jaya Publisher, 2023)
This study aims to analyze the influence of Professionalism and Facilities on Job Satisfaction with Employee Performance as an intervening variable. This research was conducted at the North Binjai District Office. The population in this study were 80 employees and the sample used was a saturated sample. The research model used is the path analysis measuring tool using smart PLS version 3.3.3. The results of this study are work facilities have a positive and significant effect on job satisfaction. Facilities have no significant positive effect on employee performance. Employee Performance has no significant negative effect on Job Satisfaction. Professionalism has a positive and significant effect on job satisfaction. Professionalism has a positive and significant effect on employee performance. Work facilities have a negative and insignificant effect on job satisfaction through employee performance. Professionalism has no significant negative effect on Job Satisfaction through Employee Performance.